AKIBAT HUKUM PEMBATALAN KERJASAMA ANTARA PROMOTOR KONSER DENGAN ARTIS AKIBAT PANDEMI COVID-19 - Mohammad Dipa Fahmi Lazuardi; Rosalinda Elsina Latumahina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
A music concert event is currently one of the community's sources of entertainment. Because a music event allows followers of a singer and/or band, both local and worldwide performers, to see their idols live. Furthermore, the atmosphere of a music concert can undoubtedly create an impression and experience for the audience. A music performance event will never be devoid of admirers due to the interdependence of these components. Another factor supporting the continued existence of music concerts is the growing public desire for music. The various music performances held in both festival and tour styles, both in Indonesia and abroad, demonstrate the vibrancy of a musical performance. Similarly, there is a high level of public interest in purchasing musical tickets. Every time a music event is held, hundreds or even tens of thousands of people pack the venue. Due to overwhelming demand from the public, promoters frequently lengthen the time of music concerts. One essential factor driving the music industry's rapid expansion is the preservation of solid cooperative relationships between concert promoters and performers." This cooperative partnership concerns the parties' rights and obligations, as well as certain provisions that must be followed. In order for a cooperative relationship to function properly, an agreement or cooperation contract must be used as a medium or instrument to accommodate multiple existing interests. So that it may ensure that all parties' interests are met and no one is hurt. Because all parties fulfill their rights and obligations, the foregoing conditions might be considered perfect in a cooperative relationship. The Covid-19 epidemic, on the other hand, compelled the parties involved by the collaboration agreement contract to execute their rights and obligations. Overall, the Covid-19 pandemic resulted in numerous unexpected cancellations of collaboration, resulting in both material and non-material losses. This study will look at the legal ramifications of event promoters and artists terminating their collaboration owing to the Covid-19 outbreak. The goal of this research is to examine the legal ramifications of event promoters and musicians canceling collaboration because of the Covid-19 outbreak. This study employs a normative juridical methodology using a statutory and conceptual approach, as well as primary, secondary, and tertiary legal materials. This research uses qualitative analysis to obtain legal materials through literature studies. According to the findings of this study, there must be regulations in an agreement or cooperation contract that foresee cancellations due to things beyond the control of the parties involved and non-natural disasters such as the Covid-19